Pengaruh Perilaku Pemimpin Komitmen Guru terhadap Prestasi Kerja pada MTSN Terusan Kecamatan Muara Bulian - Endang Meliani; Afriantoni Afriantoni (Universitas Batanghari Jambi, 2019)
The purpose of this study is to explain the influence of Leaders Behavior and Teacher Commitment to Job Performance in MTs Negeri Terusan Muara Bulian Subdistrict. The analytical method used is quantitative using multiple linear regression analysis tools. The test of significance of influence of Leader Behavior variable (X1) and Teacher Commitment (X2) as independent variable, and Work Achievement (Y) as the dependent variable is done T Test and F Test. The result of hypothesis testing on the effect of Leader Behavior and Teacher Commitment to Work Achievement that the value of t arithmetic is 2,139 > from the t table number 2,05183 and the significance level of (α) 0.05 (5%) it can be seen that this Leader Behavior has influence on Job Performance. The result of hypothesis testing on the basis of the variable Teacher Commitment to Work Achievement that the value of t arithmetic amounted to -1.728 and with a significant level of 5% obtained t table 2.05183 it can be seen that the value of t arithmetic of -1.728 > from number t table 2.05183 and number of significance of 0.05 (5%) it is known that this Master's Commitment has an effect on Work Achievement. The result of hypothesis test on Lead Behavior variable and Teacher Commitment to Work Achievement showed that F value obtained by F value 2,372 with significance level 0,05 value f table 3,34 this mean that F count (2.372 > F table (3,34) thus Ho is rejected and Ha accepted, meaning that Leader Behavior (X1) and Teacher Commitment (X2) have a positive effect simultaneously or together on Work Achievement at MTs Negeri Terusan Muara Bulian Subdistrict Adjusted R Square is 0,86. So it can be concluded the percentage of influence of Leaders Behavior and Teacher Commitment to Job Performance in MTs Negeri Terusan of 0.86% and 91.4% in influencing other variables not examined in this study.